Implementasi Pendidikan Life Skill pada Sekolah Dasar Inklusif di Provinsi Banten - Imas Mastoah; Devi Saputri; Nijma Aprilita (Journal on Education, 2023)
This study aims to photograph the implementation of life cycle education that has been carried out in inclusive primary schools, and to describe the activities and skills of the implementation process that have been implemented in inclusive schools. The subjects in this study were teachers from class 1 to class V, the number of samples interviewed was 6 teacher boards and one PLP student. Data collection methods used by researchers are interviews, observations, and supporting documents while on location. Analysis of the data obtained from the implementation of life skills education. including the main skills, namely self-knowledge skills, academic skills (and thinking skills) and social skills. Seeing the implementation of life skill activities that have been carried out properly since the school was founded. In the Cilegon city civilization school, it has been integrated with two curricula, namely the 2013 curriculum and the school curriculum. The two curricula already include extracurricular and regular learning activities. The analysis of the results of this study can be concluded as follows: that the implementation of life skills education is very important to be taught to elementary school children who provide inclusive education. This has also been applied by parents to their children since entering civilization elementary schools. The hope is that in the future parents are advised to be able to establish good cooperation regarding the implementation of life skills education.